Pedagogy and Materials for Teaching Piano to Children in China and the United States - (:unkn) unknown (My University, 2015)
This qualitative study compared the pedagogical teaching practices and piano materials used by five Chinese and two U.S. piano teachers. The teacher interviews were conducted in China and the United States based on semi-structured questions and then transcribed, translated as needed and interpreted for common themes. Interviews revealed details about specific pedagogical practices that are different based on the age of piano students, individual teacher ideas about selection of materials, and the impact of developing relationships and motivation for students. The piano materials revealed a lack of different material in the books published in the United States and China. The Chinese materials were identical in content except for the translation of written text into Chinese. Images in the books were also identical. Implications suggest that inclusion of Chinese musical material in the piano books would allow teachers to introduce finger patterns for pentatonic scales and also provide students with an introduction to the harmonic and stylistic characteristics of Chinese music in the early development of piano playing.
Keywords: China; Music Education; Piano Teaching